THE INFLUENCE OF WORKSHOP MANAGEMENT ON THE SKILLS OF STUDENTS OF SMK NEGERI 3 TORAJA UTARA - Mardos, Harlan; Nadeak, Bernadetha (International Journal of Research -GRANTHAALAYAH, 2021)
This research aims to find out the influence of workshop management on SMK Negeri 3 Toraja Utara skills. This research is a quantitative research survey: systematic scientific research on parts and phenomena and their relationships. The design was chosen because following the nature of the research conducted at first. The research on the relationship between workshop management was conducted to improve students' skills at SMKN 3 Toraja Utara. The research results explained that there is an influence of workshop management on the skills of students of SMK Negeri 3 Toraja Utara, based on the results of the t-test of 5,623 with a significant 0.035